Is the development of liquid biopsy for the early detection and the monitoring of breast cancers on its way of overtaking mammography? - Mansour, Hicham; Nejjari, Chakib; Incitti, Roberto; Anouar, Naima; Ouhajjou, Abdelhak (Frontiers in Medicine, 2024)
Mammography, as of today, is used as gold standard for screening, diagnosing and monitoring breast cancer (BC). While being overall beneficial, it has several downsides, like limitation in accuracy, relatively high cost and the dependence on a heavy infrastructure, hence a lesser accessibility to the entire global target population. There is currently no established alternative to mammography and overcoming this major challenge is a hot research and technology topic. One of the avenues for tackling this issue, is the development of highly sensitive and specific non-invasive blood tests for the early diagnosis and the follow up of breast cancer. This paper discusses the limitations of mammography and recapitulates the blood tests already available, under development and the future developments in this field.